ANALYSIS OF SHORT AND MEDIUM TERM COASTAL ABRASION AND ACCRETION RATES USING GIS IN KARAWANG, WEST JAVA - Fauzie, Azis Kemal (Badan Penelitian dan Pengembangan Daerah Provinsi Jawa Barat, 2017)
A GIS-based study was performed to examine the short- and medium-term effects of coastal abrasion in Karawang, West Java. In short-term assessment the trends varied every nine year period. The equal rates were identified between 1988 and 1997 when both abrasion and accretion occurred with rate of 12 ha/year. In the period between 1997 and 2006 the accretion has dominated by causing emerging land of around 27 ha/year, while erosion only displaced 2 ha/year of coastal area. Between 2006 and 2015, further abrasion occurred with rate of approximately 15 ha/year, while accretion rate was only 8 ha/year. Medium-term analysis between 1988 and 2015 suggested that abrasion has affected on area loss with rate of over 15 ha/year, while accretion gave additional land with rate double than abrasion rate at the same period. A brief schematic design of beach protection structures has been provided in the study as alternative option to minimize the future impacts of coastal erosion by incorporating natural and artificial measures.